DNA Based Vaccine Expressing SARS-CoV-2 Spike-CD40L Fusion Protein Confers Protection Against Challenge in a Syrian Hamster Model - Tamming, Levi A.; Duque, Diana; Tran, Anh; Zhang, Wanyue; Pfeifle, Annabelle; Laryea, Emmanuel; Wu, Jianguo; Raman, Sathya N. Thulasi; Gravel, Caroline; Russell, Marsha S.; Hashem, Anwar M.; Alsulaiman, Reem M.; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 infections present a tremendous threat to public health. Safe and efficacious vaccines are the most effective means in preventing the infections. A variety of vaccines have demonstrated excellent efficacy and safety around the globe. Yet, development of alternative forms of vaccines remains beneficial, particularly those with simpler production processes, less stringent storage conditions, and the capability of being used in heterologous prime/boost regimens which have shown improved efficacy against many diseases. Here we reported a novel DNA vaccine comprised of the SARS-CoV-2 spike protein fused with CD40 ligand (CD40L) serving as both a targeting ligand and molecular adjuvant. A single intramuscular injection in Syrian hamsters induced significant neutralizing antibodies 3-weeks after vaccination, with a boost substantially improving immune responses. Moreover, the vaccine also reduced weight loss and suppressed viral replication in the lungs and nasal turbinates of challenged animals. Finally, the incorporation of CD40L into the DNA vaccine was shown to reduce lung pathology more effectively than the DNA vaccine devoid of CD40L. These results collectively indicate that this DNA vaccine candidate could be further explored because of its efficacy and known safety profile.